The cultural life of kurds according to the writers of foreign travelers in the qajar era (1796-1925) - Youssef, Fakher; Khalandi, Anwar (Humanities Journal of University of Zakho, 2024)
The increasing number of foreigners entered Iran, especially the Europeans in the 19th Century A.D. enabled them to know more about the Iranian society. Moreover, the writers of Foreign travelers who got interested in the social and cultural issues of Iran about which recorded important information. For example, the Kurds, one of the ancient Iranian tribes, attracted many foreign tourists, especially the Europeans, the Americans, and the Japanese to come to Iran in the Qajar Era. The present study aimed at shedding light on the cultural life of Kurds according to the writers of foreign travelers in the Qajar era depending on the works and observations of those travelers when visited the Kurdish regions in Iran. Moreover, such recordings were in the form of stories and traveling. An analytical and descriptive approach was adopted. Data were collected from the books on the foreign traveler in the Qajar era. As a matter of fact, the cultural life of Kurds which discussed by such writers in detail includes ethical characters, language,